Catalysts of change: Modelling teacher leadership for educational reform in the model teacher leadership in Shandong nursing educators - Xia Xu; Mat Rahimi Yusof; Farah Mohamad Zain (Environment and Social Psychology, 2025)
This study explores the multidimensional concept of teacher leadership among nursing college lecturersin Shandong Province, China. However, various barriers continue to impede the development of teacherleadership in China. These include inadequate policy support, limited professional training, and low levels ofteacher awareness regarding leadership roles. Therefore, this study aims to develop a measurement model fornursing teacher leadership. A quantitative cross-sectional survey design was employed, involving 266nursing college educators. Data were collected using a five-point Likert scale questionnaire comprising 42measurement items, which were validated through face and content validity assessments, and analyzed usingConfirmatory Factor Analysis (CFA) to ensure the reliability and validity of the constructs with the aid ofSEM Amos software.Through the reliability analysis, the findings indicated that all constructs achievedstrong reliability, with Cronbach's alpha values ranging from 0.837 to 0.963. In addition, this studysuccessfully developed a Nursing Teacher Leadership measurement model and validated 41 leadershipbehaviours encompassing dimensions such as self-awareness, change leadership, communication, diversity,instructional proficiency, and continuous improvement. These leadership behaviours among nursing lecturerswere confirmed. The findings suggest that educators are ready to take on greater roles in decision-making,yet there is a need for professional development programs to enhance their instructional competencies.Thisstudy is expected to contribute to the literature on teacher leadership by providing empirical evidence from,the Chinese context and emphasizing the importance of comprehensive support systems to developleadership skills among nursing educators. Future research is recommended to expand the study acrossnursing colleges throughout China to allow for broader generalization of the findings.